On Judicial Review and Democratic Authority: Dedication to a Process - Coletti, Aaron J. (My University, 2023)
Dedication to a Process argues that while judicial review is a justified decision-making procedure in a democratic scheme of government on instrumentalist grounds, it will always come at a politico-moral cost. Chapter One surveys Thomas Christiano’s egalitarian conception of democracy to establish a scheme of democracy upon which to ground this analysis. This chapter argues that under Christiano’s account of the normative grounds of democracy, which is rooted in the fundamental social justice principle of public equality, there are necessary limits to democratic authority. When these limits are exceeded, there is a results-based argument available that can justify the use of judicial review from a Razian perspective, however, this manner of decision-making comes at the concession of a significant politico-moral value that is bound up with democratic authority: intrinsic justice. Chapter Two analyzes Ronald Dworkin’s constitutional conception of democracy to determine if there is a way to pay down the cost of judicial review. This chapter will argue that a purely content-based analysis like the one Dworkin is suggesting with his holistic scheme of democratic authority may be able to avoid the loss of intrinsic justice. However, if we are more concerned not with content but with who the authoritative voice is on constitutional matters, as is the case with Christiano’s modular scheme of democratic authority, then we must revert to the conclusion reached in Chapter One. Chapter Three considers Wil Waluchow’s theory of Community Constitutional Morality to rule out the possibility that judges appealing to a community’s positive normative commitments as a kind of customary constitutional law can be grounded in public equality, thereby retaining democratic authority and avoiding the politico-moral cost established in Chapter One. This chapter will argue, however, that despite passing the Public Equality Test mechanically, there is an important value argument to be made that locates intrinsic justice within characteristically democratic institutions such as the legislature and that any compromise of the democratic process must result in a politico-moral loss if we are indeed dedicated to the process.
Keywords: Judicial review; Democratic authority; Judicial justification; Public equality; Constitutional law